KAJIAN PENANGANAN BENCANA DI DINAS SOSIAL KABUPATEN MUSI RAWAS SUMATERA SELATAN - R A Zubaidah; Yohanes Susanto; Bambang Setiono (LPPM UNIVERSITAS BINA INSAN, 2020)
The purpose of this study is to empirically examine disaster management carried out by the Regional Government in this case the Social Service Office of Musi Rawas Regency, South Sumatra. This research is a qualitative study using a type of research with case studies. The subject of the case study is the analysis of disaster management planning with other words Analysis of Disaster Management Planning is the Focus of this Research. To support the focus of research, the researcher makes sub-focus - sub focus, to represent and better direct the focus of the research, while the sub focus - the sub focus consists of; The planning process is carried out; Structured and planned planning. And planning that is ongoing and sustainable. Results of research findings, that based on several theories and research findings, it can be seen that the process of disaster management planning in the Social Office of musi rawas district is oriented to the process of activities within the Social Service alone, no process has yet been seen involving other parties. Coordination with related agencies has not been reflected in the understanding of planning in the Musi Rawas Regency Social Service. It is recommended that related parties in cross-sectoral in Musi Rawas Regency be involved in the process of disaster management planning in the Musi Rawas Regency Social Service.